2018
DOI: 10.1155/2018/6523653
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of the Third-LineHelicobacter pyloriEradication

Abstract: Antibiotic resistance is growing worldwide, and patients who have failed consecutive 1st- and 2nd-line H. pylori eradication regimens are increasing. Therefore, the role of the bacterial culture with antibiotic susceptibility testing and molecular susceptibility testing is important for avoiding the use of ineffective antibiotics. However, antibiotic susceptibility testing-guided treatment does not necessarily guarantee successful eradication, and there have been mixed results for the effectiveness of a 3rd-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 63 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…In CVID, serological tests are not useful to identify H. pylori positive patients and only direct diagnostic methods for H. pylori detection should be considered ( 23 ). However, follow-up strategies targeted at gastric cancer secondary prevention cannot rely only on H. pylori identification, since the eradication of H. pylori might not abolish the risk for neoplastic progression ( 24 26 ). This is supported by our observation in two CVID patients who developed gastric cancer 1–2 years after a H. pylori -negative gastric biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…In CVID, serological tests are not useful to identify H. pylori positive patients and only direct diagnostic methods for H. pylori detection should be considered ( 23 ). However, follow-up strategies targeted at gastric cancer secondary prevention cannot rely only on H. pylori identification, since the eradication of H. pylori might not abolish the risk for neoplastic progression ( 24 26 ). This is supported by our observation in two CVID patients who developed gastric cancer 1–2 years after a H. pylori -negative gastric biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…[28] Moreover, there is no definite 2nd-line or 3rd-line rescue regimen for patients who do not respond to the above therapies. [17] Fluoroquinolone- and rifabutin-containing regimens or a combination of bismuth with different antibiotics is the remaining empirical option. [8,17] However, the antibiotic resistance rates in Korea of ciprofloxacin, levofloxacin, and moxifloxacin are reported to be up to 38.2%, 37.7%, and 34.6%, respectively, which are higher than those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[9,16] Moreover, dual clarithromycin and metronidazole resistance undermines the efficacy of concomitant therapy, and there is no definite 2nd-line or 3rd-line rescue regimen for patients who do not respond to the above therapies. [17,18] Therefore, finding an optimal regimen for 1st-line eradication is warranted in Korea.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the bacterium is present in almost all patients with active chronic gastritis, duodenal ulcer and gastric ulcer; thus, it may be a significant factor in the etiology of these diseases. Therefore, eradication of H. pylori in infected patients is very important for the treatment of diseases associated with this agent (3). For the treatment and eradication of this infectious agent, the conventional approach relies on using multiple antibiotics such as clarithromycin, amoxicillin, tetracycline, metronidazole in combination with bismuth sulphate or a proton-pump inhibitor (4).…”
Section: Introductionmentioning
confidence: 99%